1999
DOI: 10.1016/s0165-232x(99)00013-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the microstructural and micromechanical properties of snow

Abstract: ABSTRACT:A micropenetrometer has been developed that produces snow grain bond ruptures at the microstructural level and provides a unique signal for different snow types . A micromechanical theory of penetration has been developed and used to recover microstructural and micromechanical parameters for different snow types from the penetration force-distance signal. These parameters are the microstructural element dimension, the mean grain size, the critical microstructural deflection at rupture and the microstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
110
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 4 publications
1
110
1
Order By: Relevance
“…For instance, Brown (1980) investigated the snow reaction forces of the neck bindings between snow grains of sintered snow. Johnson and Schneebeli (1999) modeled the penetration force as F ¼ Nf with N the number and f the contribution of each intact microstructural element. Both works support the hypothesis that the snow reaction force against compression is proportional to its volume change.…”
Section: Snow Hardness and Failure Shear Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Brown (1980) investigated the snow reaction forces of the neck bindings between snow grains of sintered snow. Johnson and Schneebeli (1999) modeled the penetration force as F ¼ Nf with N the number and f the contribution of each intact microstructural element. Both works support the hypothesis that the snow reaction force against compression is proportional to its volume change.…”
Section: Snow Hardness and Failure Shear Stressmentioning
confidence: 99%
“…Johnson and Schneebeli (1999) related the overall reaction force to micromechanical parameters of the snow. In particular, they modeled the penetration force as F ¼ Nf , with N the number of bonds between the snow particles and f the contribution of each element.…”
Section: Introductionmentioning
confidence: 99%
“…It provides a penetration resistance (force)-depth signal that includes micro-structural information (Johnson and Schneebeli, 1999;Marshall and Johnson, 2009). Mechanical properties can be derived from the three basic micro-structural parameters: element length (L), deflection at rupture (δ) and rupture force (f ).…”
Section: Introductionmentioning
confidence: 99%
“…From the graph it may appear that large-plate data are not recorded until a depth of 0.14 m; however, inspection of the raw data suggests that fluctuating resistance of $5 to 10 kPa was measured at this time; whether this is a true representation of resistance at this shallow depth is not known. Kinosita (1964) and Johnson and Schneebeli (1999) have shown that variations in cone shape affect measured resistance values, both in snow and soils. In order to verify this phenomenon, some tests were conducted with a flat plate of identical diameter to the standard 608 cone; no other cone shapes were used.…”
Section: Effect Of Penetrometer Sizementioning
confidence: 99%
“…Fukue, 1977) supports this. Penetrometer size affects measured stress in soils (Whiteley and Dexter, 1981), and Johnson and Schneebeli (1999) modelled size effects in granular materials, so it is probable that both cone size and shape will affect measured stress in snow.…”
Section: Introductionmentioning
confidence: 99%